Gestión de ventas en Centertech-Pc - Armijo Bravo, Yuleisy Stefania (2021)
The present investigation was carried out at the CenterTech-PC company of the Canton Montalvo dedicated to the retail sale of telecommunications equipment, laptops, cell phones, peripheral accessories, it also offers repair and maintenance services. The objective of the case study is to know the problems concerning sales management since they present factors that negatively affect the company, due to the fact that sales processes are not established, the staff is not properly trained to be able to offer a good customer service and therefore failing to generate interest in making a purchase in the establishment. Through the qualitative method, information can be obtained to analyze it and describe in detail the situations of the raised issue. For this reason, the techniques of surveys directed towards the personnel and the interview towards the owner manager of CenterTech-PC were used, in which the following results were obtained, there is more and more competition and the establishment does not have products that differentiate them of the rest, it does not create strategies to be able to capture the customer's attention and therefore its goals are not defined. Which indicates that these factors influence the decrease in sales.